Children's Spiritual Intelligence During the Covid-19 Pandemic - Cindy Sukma Dewi; Dewi Nurmala Sari (Journal of Contemporary Islamic Primary Education, 2022)
Every human being is created to have an element of intelligence. Intelligence is widely understood to be only intelligence, but there is still emotional intelligence and spiritual intelligence. A person's intelligence can be seen from the habituation of the students in worshiping and practicing the teachings of Islam that they know. This research was conducted to find out the various program activities carried out by the students at the Ummi Kartini III Quran House in Medan. The research method used is a descriptive qualitative method to assess the spiritual intelligence of students before the Covid 19 pandemic and after the Covid 19 pandemic. Data collection was obtained through observation, interviews, and documentation. The results showed that the spiritual intelligence of the students of the Ummi Kartini III Medan Quran House increased and developed. One of the causes is the existence of various Islamic studies and religious programs carried out at the Ummi Kartini III Medan Quran House which requires students to be better in the future in terms of worship and daily life according to Islamic teachings.